Building effective innovation systems versus dealing with market failures as ways of thinking about technology policy - Richard Nelson (The University of Manchester, Manchester Business School, 2008)
In this essay I compare two different theoretical frameworks in economics for orienting analysis of issues in technology policy. One is a neoclassical framework that sees appropriate policies as dealing with 'market failures'. The other framework is provided by an evolutionary and institutional approach to economic analysis that sees appropriate policies as building or maintaining an effective 'innovation system'. It should be no surprise that I believe the latter framework is the more useful one. I begin by laying out the key general differences between the two broad theoretical frameworks, and how they lead to different perspectives on technology policy. Then I turn to a particular case: technology policy regarding pharmaceuticals. Finally, I comment on the general question of the role of economic theories in framing policy analysis.
Keywords: 330; Forschungs- und Technologiepolitik; Innovationspolitik; Wirkungsanalyse; Wirtschaftstheorie